2009
DOI: 10.1042/bj20090121
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of GSK1070916, a potent and selective inhibitor of Aurora B and Aurora C kinases with an extremely long residence time1

Abstract: The Aurora kinases AurA, B and C are serine/threonine protein kinases that play essential roles in mitosis and cytokinesis. Among them, AurB is required for maintaining proper chromosome alignment, separation and segregation during mitosis, and regulating a number of critical processes involved in cytokinesis. AurB overexpression has been observed in a variety of cancer cell lines, and inhibition of AurB has been shown to induce tumour regression in mouse xenograft models. In the present study we report the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 25 publications
3
49
0
Order By: Relevance
“…In contrast, TAK-901 displayed a slow on-rate to inhibit Aurora B/INCENP and once formed, the TAK-901-bound Aurora B/INCENP complex dissociated slowly with a half-life of 920 minutes. This favorable biochemical property of extremely long residence time on Aurora B/INCENP was also reported recently for GSK1070916, an Aurora B/Cselective kinase inhibitor (26). Although the biochemical methods used were different, the TAK-901 dissociation rate seems of comparable magnitude with GSK1070916, whereas their kinetic analysis indicated that Aurora kinase inhibitors AZD1152 and VX-680/MK-0457 exhibit much faster dissociation rates (26).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In contrast, TAK-901 displayed a slow on-rate to inhibit Aurora B/INCENP and once formed, the TAK-901-bound Aurora B/INCENP complex dissociated slowly with a half-life of 920 minutes. This favorable biochemical property of extremely long residence time on Aurora B/INCENP was also reported recently for GSK1070916, an Aurora B/Cselective kinase inhibitor (26). Although the biochemical methods used were different, the TAK-901 dissociation rate seems of comparable magnitude with GSK1070916, whereas their kinetic analysis indicated that Aurora kinase inhibitors AZD1152 and VX-680/MK-0457 exhibit much faster dissociation rates (26).…”
Section: Discussionmentioning
confidence: 87%
“…This favorable biochemical property of extremely long residence time on Aurora B/INCENP was also reported recently for GSK1070916, an Aurora B/Cselective kinase inhibitor (26). Although the biochemical methods used were different, the TAK-901 dissociation rate seems of comparable magnitude with GSK1070916, whereas their kinetic analysis indicated that Aurora kinase inhibitors AZD1152 and VX-680/MK-0457 exhibit much faster dissociation rates (26). Therefore, the Aurora B tight-binding property may be less common among reported Aurora B kinase inhibitors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Selective inhibitors of Aurora B have been developed: AZD1152 [136] (highly potent and selective inhibitor of Aurora B), and GSK1070916 (a potent and selective inhibitor of Aurora B and Aurora C kinases) [137]. The general chemical structures of selective Aurora B inhibitors are shown in (Fig.…”
Section: Selective Aurora B Inhibitorsmentioning
confidence: 99%
“…One clue to the proper correlation between in vitro and in vivo drug activity is the dissociation rate, which may better describe cellular efficacy than K D and IC 50 among kinase inhibitors and other type of enzyme inhibitors such as proteases. 3,15 A good example of this is given in the study of the AIDS drug saquinavir. Although saquinavir is an effective HIV protease inhibitor in treating AIDS, resistant mutants arise through the treatment.…”
Section: Implications For Evaluation Of Kinase Inhibitorsmentioning
confidence: 99%